History, citoarchitecture and neurophysiology of human and non human primates' parietal lobe: A review - Aversi-Ferreira,Tales Alexandre (2010)
Abstract This strict localizationism had and still has its importance for the development of Neurosciences, since the analysis of changes in mental processes resulting from brain damage became the basis for understanding the brain organization. The human parietal cortex is a highly differentiated structure, consisting of citoarchitectonically defined subareas that are connected to other cortical and subcortical areas. Patients with lesions in the parietal cortex develop various types of neuropsychological manifestations, depending on the specific location of the lesion and the corresponding hemisphere and these lesions in this lobe do not cause modal specific disturbances. The establishment of homologies between the parietal region in humans and primates can be of great contribution in trying to unravel the various functions and complexity of this area.